Wicked lies - Jackson, Lisa.; Bush, Nancy, 1953- (New York : Zebra Books, 2011)
When reporter Harrison Frost begins interrogating Laura Adderley about her involvement in the Colony's sordid past, she vows to protect her unborn child at all costs from both him and an escaped psychopath bent on killing her.
Includes excerpts from: Born to die by Lisa Jackson and Hush by Nancy Bush.
Keywords: Pregnant women -- Fiction; Journalists -- Fiction; Psychopaths -- Fiction; Suspense fiction